2015
DOI: 10.18632/oncotarget.4360
|View full text |Cite
|
Sign up to set email alerts
|

Embigin, regulated by HOXC8, plays a suppressive role in breast tumorigenesis

Abstract: The transmembrane glycoprotein embigin (EMB) belongs to the immunoglobulin superfamily (IgSF) and a number of IgSF members have been identified as biomarkers for cancer progression. In this study, we show that embigin is transcriptionally regulated by Homeobox C8 (HOXC8) in breast cancer cells and embigin expression suppresses breast tumorigenesis. With aid of Western blot, luciferase reporter gene assay and chromatin immunoprecipitation, we reveal that HOXC8 binds to the EMB promoter at the region of nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…3g). EMB (Embigin) encodes a transmembrane protein belonging to the immunoglobulin superfamily that has been identified as a biomarker for cancer progression35. In addition to the potential pathogenic role of circ_RMB, the conversion of linear EMB transcript to circRNAs via back-splicing might also serve to decrease the protein output and thereby lead to excessive cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…3g). EMB (Embigin) encodes a transmembrane protein belonging to the immunoglobulin superfamily that has been identified as a biomarker for cancer progression35. In addition to the potential pathogenic role of circ_RMB, the conversion of linear EMB transcript to circRNAs via back-splicing might also serve to decrease the protein output and thereby lead to excessive cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…LY6D protein initiates the first stage of B cell development [ 57 ] while MUC1 protein plays important roles in the first line defense against invading pathogens [ 58 ]. Meanwhile, EMB and EYA2 have important roles in development processes [ 59 , 60 ]. As expected, DE genes were enriched in many biological processes related to regulation of biological and cellular processes, which reflect the major developmental changes in the physiology and functions of the rumen from pre- to post-weaning stages ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the HOX family, HOXC8 functions as a transcriptional activator to induce the expression of several genes, including osteopontin (OPN), neural cell adhesion molecule (NCAM), proliferating cell nuclear antigen (PCNA), and CDH11 [ 33 , 34 ]. It has also been reported that HOXC8 acts as a transcriptional repressor to downregulate the expression of Mgl1, Smad6 and embigin [ 35 37 ]. Since CDH11 is expressed only in invasive breast cancer cells and HOXC8 acts as either a transcriptional activator or repressor, we speculated that HOXC8 associated with other proteins to activate CDH11 transcription in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%